2013
DOI: 10.3109/10717544.2013.838713
|View full text |Cite
|
Sign up to set email alerts
|

Insights into direct nose to brain delivery: current status and future perspective

Abstract: Now a day's intranasal (i.n) drug delivery is emerging as a reliable method to bypass the bloodbrain barrier (BBB) and deliver a wide range of therapeutic agents including both small and large molecules, growth factors, viral vectors and even stem cells to the brain and has shown therapeutic effects in both animals and humans. This route involves the olfactory or trigeminal nerve systems which initiate in the brain and terminate in the nasal cavity at the olfactory neuroepithelium or respiratory epithelium. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
128
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(136 citation statements)
references
References 67 publications
0
128
0
1
Order By: Relevance
“…Others have reviewed the intranasal delivery of a wide range of commercially available pharmaceuticals (13,16). They highlight some of the kinetics involved in determining the transport rate of the various drugs after intranasal delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Others have reviewed the intranasal delivery of a wide range of commercially available pharmaceuticals (13,16). They highlight some of the kinetics involved in determining the transport rate of the various drugs after intranasal delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, intranasal drug delivery is verified as a reliable method to bypass the blood-brain barrier (BBB) and deliver therapeutic drug to the brain and has shown therapeutic effects in both animals and humans (Mittal et al, 2014). Other researchers of our group have found that, either methotrexate or apomorphine after intranasal administration, the brain targeting index were significantly higher than other routes of administration (e.g.…”
Section: Introductionmentioning
confidence: 91%
“…Various strategies have been experimented to overcome the low brain permeability of CNS therapeutic agents (Kasinathan et al, 2014;Mittal et al, 2014). Prodrug strategy, one of the medicinal chemistry drug delivery systems, has been investigated extensively in order to increase the targeting efficiency of drugs to the brain (Anderson, 1996).…”
Section: Discussionmentioning
confidence: 99%